Формування культури академічної доброчесності у здобувачів аграрних закладів вищої освіти - Шарова, Тетяна Михайлівна; Sharova, Tetiana (My University, 2025)
UA: У статті розглядається проблема формування культури академічної доброчесності у здобувачів вищої освіти аграрних закладів. Наголошено на значущості академічної доброчесності як складової якісної підготовки майбутніх фахівців аграрного сектору. Проаналізовано основні напрями формування доброчесної поведінки здобувачів освіти, зокрема інтеграцію етичних норм в освітній процес, залучення до наукової діяльності, використання цифрових інструментів, участь у розробленні внутрішніх кодексів етики та роль викладача як носія академічних цінностей. Акцентовано на необхідності комплексного підходу до формування внутрішньої мотивації до дотримання принципів доброчесності як запоруки професійного становлення та суспільної відповідальності майбутніх аграріїв. /// EN: The article addresses the issue of developing a culture of academic integrity among students in agricultural institutions of higher education. The significance of academic integrity as an essential component of the high-quality training of future professionals in the agricultural sector is emphasized. The main directions for fostering students’ ethical behavior are analyzed, including the integration of ethical standards into the educational process, engagement in scientific research, the use of digital tools, participation in the development of internal codes of ethics, and the role of the teacher as a bearer of academic values. The need for a comprehensive approach to cultivating internal motivation for adhering to the principles of academic integrity is underlined, as this serves as a foundation for professional development and social responsibility of future agricultural specialists.
Formation of academic integrity culture among higher education students in agricultural institutions
Keywords: академічна доброчесність; вища аграрна освіта; культура доброчесності; здобувач освіти; етика; академічне письмо; academic integrity; higher agricultural education; integrity culture; student; ethics; academic writing